Education scientific poster training with Canva assistance for UPI Purwakarta students - Dwi Wahyu Riani; Syifaul Fuada; Isni Putri; Eka Novelia Putri Arini; Husnul Ulfa; Delia Fitri Setiani; Eildila Shalsadiza Pradiptya; Mahmudah Salwa Gianti (Community Empowerment, 2023)
Scientific poster training with Canva aims to increase students knowledge and skills in making scientific posters as well as being a competition for participants in implementing their new skill. The method used is to form a training concept as well as a scientific poster competition involving the role of LEPPIM management and members as the committee. This training and competition activity was attended by 20 students online using the Zoom Meeting platform and the Google Form link as a means to collect works. The result of this training is increasing the knowledge and sportsmanship of the participants in competing to produce scientific poster works.